Clinical and economic evaluation of the effectiveness of tension-free methods of inguinal hernioplasty - V. V. Darvin; A. N. Poborskiy; Sh. D. Asutaev (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to determine the optimal approaches to the choice of the method of tension-free inguinal hernioplasty based on the clinical and economic analysis. METHODS AND MATERIALS. A comparative study of the results of treatment of 95 male patients with primary unilateral inguinal hernia using the Lichtenstein method and TAPP was carried out. Before surgery and a year later, patients’ quality of life parameters were assessed using the EQ-5D questionnaire and used to calculate QALY (Quality Adjusted Life Years), the growth of which during the year served as a criterion for the effectiveness of the analyzed surgical technologies. A cost-utility analysis was carried out using direct costs. RESULTS. With a 34 % higher cost of endoscopic hernioplasty compared to the operation using the Lichtenstein method, the effectiveness of TAPP was higher, which manifested itself in a more significant increase in the quality of life of patients in the postoperative period. The calculated cost-utility ratio also turned out to be 15 % higher with TAPP. Correlating the result of the incremental cost-utility analysis carried out below with the value of the «willingness to pay threshold» demonstrated the financial acceptability of TAPP. The value of the incremental indicator under TAPP not only did not exceed the «willingness to pay threshold», but was also 49 % lower than the value of GDP per capita. CONCLUSION. The cost-utility analysis showed that regardless of cost fluctuations and changes in patients’ quality of life, the more expensive endoscopic TAPP intervention for inguinal hernia is economically justified, proving to be a profitable investment.